System of Interconnections of the Achievement Motivation with the Sports Results of the Young Karate Enthusiasts - Osika, K. S. (Psychological Prospects Journal, 2012)
System of interconnections of the achievement motivation with the sports results of the young karate enthusiasts during the crucial competitions is considered in the article. Correlation coefficients between different categories of the achievement motivation and the level of the sports qualification of the karate enthusiasts of different age groups as well as correlation coefficients between the level of sports qualification and the results of the sport competitions of the young karate enthusiasts and the correlation of the categories of self-actualization of sportsmen at the beginning and at the end of the formation experiment are represented in the article. Rank places of the categories of self-actualization of sportsmen at the beginning and at the end of the formation experiment are represented. Galaxy correlation between achievement motivation (desire for success) categories and the level of sports qualification as well as the galaxy correlation between the achievement motivation categories (avoidance of failure) and the sports qualification level of the young karate enthusiasts was